In the Mists of Time: Searching for traces of the first settlement of four Southland families - Mackay, Christina (Architectural History Aotearoa, 2018)
During the 1870s, the Provincial government terminated grazing licences on large runs in Eastern Southland and West Otago. In a series of land sales, this land was surveyed into 200-acre farms and auctioned to prospective farmers on a delayed repayment scheme. 150 years later, this research searches for traces of the first buildings from this time. It focuses on the housing of eight ancestors, great grandparents of the author, who settled within a 30 km radius in the districts of Waikoikoi, Maitland, Waikaka Valley and Otama. Information was gathered from National Library collections, district and family history books, old photographs and maps, 2018 surveys of the homestead sites and interviews with cousins still living in the area. In 1870, the rolling hills were covered with open tussock. Found artefacts suggest that Māori camped in the area during expeditions to gather food from Mataura river sites. The new settlers, often in extended family groups, travelled by horse and dray overland from Dunedin or Bluff. The Dunedin to Gore railway did not open until 1879. Their first shelters were camp-sites and wagon tilts lined in felt. Soon after they arrived, established families were able to fund the building of modest timber houses often constructed by carpenter uncles and brothers. Young single men "bached" in sod and/or timber huts until they married. One great grandmother spent childhood years "comfortably" in a "half-sod and half-timber shepherd’s cottage" but her teenage years at the "Big House," the 20-room homestead on the Otama Station. It was built in 1867 of "white pine" from the forest at Tapanui. By the turn of the twentieth-century, simple cottages had received additional rooms, porches and decorative verandahs or they were upstaged by new grand timber villas. In 2018, only one homestead, originally named Hopetoun, is still standing although it is substantially altered. Family photographs, usually of the front façade, provide a limited perspective only. Memoirs and local histories offer a few more clues. While buildings from the 1870s exist, historical touchstones in these country districts are more elusive.